46.5k views
3 votes
What is the simplified Expression of -2/3(12c-9)+14c

User Dannie
by
5.1k points

2 Answers

4 votes

Answer:

6(c + 1)

Explanation:

Given:
$ - (2)/(3) (\ 12c - 9 )\ + 14c $.

Distributing
$ - (2)/(3)$ over
$ 12c - 9 $ we get:


$ - (2)/(3) (12c) + (2)/(3) (9) + 14c $.

On simplifying we get:
$ -2(4c) + 2(3) + 14c $


$ \implies -8c + 6 + 14c = 6c + 6 = 6(c + 1) $

Therefore the answer is
$ 6(c + 1) $.

User Incepter
by
4.7k points
3 votes

Answer:

=6(1 + c)

Explanation:

Given that:

= -2/3(12c-9)+14c

By simplifying:

Negative sign before bracket will alter the inner signs

=-24c/3 + 18/3 +14c

= -8c + 6 + 14c

= 6 + 6c

By taking 6 common:

=6(1 + c)

I hope it will help you!

User Pooria Haddad
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.